1981
DOI: 10.1139/e81-037
|View full text |Cite
|
Sign up to set email alerts
|

Mélange development in the Boones Point Complex, north-central Newfoundland

Abstract: The Boones Point Complex in north-central Newfoundland is a narrow mélange belt separating Roberts Arm terrain volcanic and volcaniclastic rocks to the north from Upper Ordovician westerly derived clastic rocks to the south and east. The mélange has a sedimentary matrix and contains a polymict assemblage of blocks. Limestone blocks have yielded Llanvirn–Llandeilo conodont faunas. Sedimentologic and structural analyses indicate that the complex is composed of subaqueous debris flow deposits, which are the proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Sample 10Ca162 is an immature, coarse-grained sandstone from the Upper Ordovician Point Leamington Formation, located south of the Red Indian Line; the Point Leamington Formation is here characterized by broken formation that was grouped with the Boones Point Complex by Nelson (1981 (Figs. 2d, 3e).…”
Section: Samples Near the Iapetus Suturementioning
confidence: 99%
“…Sample 10Ca162 is an immature, coarse-grained sandstone from the Upper Ordovician Point Leamington Formation, located south of the Red Indian Line; the Point Leamington Formation is here characterized by broken formation that was grouped with the Boones Point Complex by Nelson (1981 (Figs. 2d, 3e).…”
Section: Samples Near the Iapetus Suturementioning
confidence: 99%
“…Paleocurrent evidence shows basin axis-parallel flow mostly to northeasterly through southerly directions (Helwig 1967(Helwig , 1969Nelson 1979;Arnott 1983); slump structures indicate a southeasterly downslope direction in the New Bay area (Pickering 1987). Evidence of a component of contemporary southeast-directed thrust tectonics is found on the northwest margin of the Exploits terrane in the Sops Arm-Boones Point Mélange (Nelson 1979(Nelson , 1981 where the mélange matrix and many blocks are derived from Point Leamington turbidites, with some blocks derived from the adjacent older Roberts Arm-Chanceport terrane volcanic rocks in the thrust hanging wall. The plutonic-dominated clastic content, the paleoslope indicators, and the direct evidence of late Ordovician-early Silurian overthrusting from the northwest, show that the uplifting eroding source terrane for this foreland basin was to the northwest.…”
Section: Geologic Settingmentioning
confidence: 99%
“…If these observations apply to the whole of the western part of the Dunnage, then that mélange-forming event would be after the Caradocian (Sandbian) black shale was deposited, probably later Sandbian, and not older than about 456 Ma. However, it is known that olistostrome events occurred in the northern part of the Exploits subzone from the later Ordovician up into the Llandovery (McKerrow and Cocks 1978;Nelson 1981). It seems possible as an alternative that the disrupted materials on Camel and Knight Islands, located near or at the northwestern margin of the western Dunnage Mélange, were generated separately from, and formed at a later time than the bulk of the western Dunnage, which is not elsewhere reported to contain materials of such a young inferred age.…”
Section: Geoscience Canadamentioning
confidence: 99%
“…Fold hinges show partial rotation into shearing direction; (d) lower hemisphere equal area net showing orientations of shckenlines associated with late fault zone. (Nelson, 1981;Thurlow, 1981;Blackwood, 1982;Colman-Sadd andSwinden, 1984, Kusky andKidd, 1985;Lafrance and Williams, 1992), but Karlstrom et al (1982Karlstrom et al ( , 1983a suggested northwestward directed thrusting of the Botwood Group from southeast of the New World Island area (Fig. 2).…”
Section: Regional Extent and Timing Of Southeastward Directed Thrustingmentioning
confidence: 99%
“…2), and suggested that several of the important faults in that area formed during this (his F2) deformation episode. Nelson (1979Nelson ( , 1981 described NNW dipping syn-sedimentary thrust faults from the Badger Bay/Seal Bay area (Fig. 2), and attributed them to a post-Middle Ordovician and preDevonian back-thrusting event.…”
Section: Regional Extent and Timing Of Southeastward Directed Thrustingmentioning
confidence: 99%